2017
DOI: 10.1021/acs.jpca.7b00346
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Only Thorium Fullerene, Th@C84, Uncovered

Abstract: Only a single thorium fullerene, Th@C, has been reported to date (Akiyama, K.; et al. J. Nucl. Radiochem. Sci. 2002, 3, 151-154). Although the system was characterized by UV-vis and XANES (X-ray absorption near edge structure) spectra, its structure and properties remain unknown. In this work we used the density functional calculations to identify molecular and electronic structure of the Th@C. Series of molecular structures satisfying the ThC stoichiometric formula were studied comprising 24 IPR and 110 non-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 84 publications
3
20
0
Order By: Relevance
“…Note that, although holding a formal 4+ oxidation state, the thorium cation resides close to only three pentagons of the C 3v (8)‐C 82 cage, whereas four pentagons are indispensable for thorium(IV) coordination in typical organometallic complexes such as Th( η 5 ‐C 5 H 5 ) 4 . According to the mass spectra signals of Th@C 2 n (2 n = 74‐96) reported by Chen and coworkers, the possible structures of Th@D 3h (1)‐C 74 , Th@T d (2)‐C 76 , and Th@C s (10)‐C 84 are quickly proposed by our and other's theoretical calculations . Interestingly, we found that the Th atom in Th@D 3h (1)‐C 74 may undergo an unprecedented three‐dimensional motion in the cage .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Note that, although holding a formal 4+ oxidation state, the thorium cation resides close to only three pentagons of the C 3v (8)‐C 82 cage, whereas four pentagons are indispensable for thorium(IV) coordination in typical organometallic complexes such as Th( η 5 ‐C 5 H 5 ) 4 . According to the mass spectra signals of Th@C 2 n (2 n = 74‐96) reported by Chen and coworkers, the possible structures of Th@D 3h (1)‐C 74 , Th@T d (2)‐C 76 , and Th@C s (10)‐C 84 are quickly proposed by our and other's theoretical calculations . Interestingly, we found that the Th atom in Th@D 3h (1)‐C 74 may undergo an unprecedented three‐dimensional motion in the cage .…”
Section: Introductionmentioning
confidence: 98%
“…[23] According to the mass spectra signals of Th@C 2n (2n = 74-96) reported by Chen and coworkers, the possible structures of Th@D 3h (1)-C 74 , Th@T d (2)-C 76 , and Th@C s (10)-C 84 are quickly proposed by our and other's theoretical calculations. [13,[24][25][26] Interestingly, we found that the Th atom in Th@D 3h (1)-C 74 may undergo an unprecedented three-dimensional motion in the cage. [13] Besides the Th-EMFs, Echegoyen and coworkers recently obtained three uranium metallofullerenes U@D 3h (1)-C 74 , U@C 2 (5)-C 82 , and U@C 2v (9)-C 82 .…”
mentioning
confidence: 99%
“…[14] More actinide EMFs are only predicted by the theoretical calculations. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In particular, computational studies have disclosed the exceptional structural and bonding natures of uranium EMFs. [30][31][32][33][34][35] Significantly, Wang et al more recently prepared a large family of Th@C 2n (2n 5 74-96) by a modified arc discharge method, and for the first time, they successfully isolated Th@C 82 and unambiguously characterized its structure as Th@C 3v (8)-C 82 by X-ray crystallographic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most of them are focused on the uranium‐containing ones as exemplified by the more recent successful synthesis and X‐ray characterization of U@D 3h ‐C 74 , U@C 2 (5)‐C 82 , and U@C 2v (9)‐C 82 . More actinide EMFs are only predicted by the theoretical calculations . In particular, computational studies have disclosed the exceptional structural and bonding natures of uranium EMFs …”
Section: Introductionmentioning
confidence: 99%
“…2 The carbon fullerene and its analog have been also projected to achieve high CN, such as observed M@C60 or M@(BN)n where the metal atom directly interacts with part of cluster in those cases, [3][4][5] with similarity to Th@C84 or U@C36. [6][7][8] In addition, theoretically authenticated molecular metal-fullerenes have widespread across the group 14 clusters, [9][10][11][12][13] mainly focusing on the stability of the fullerene structures, where these fullerenes provide electrostatic field that the metal atom in those cases interacts with the fullerenes shell primarily ionically. 14 And the record of high coordination complexes involving the metal elements has been updated from 14 in U(BH4)4, 15 then to 15 in [Th(H3BNMe2BH3)4] by Daly et al, 16 and recently to 16 in CoB16 by Popov et al.…”
Section: Introductionmentioning
confidence: 99%